2002
DOI: 10.1038/sj.hdy.6800031
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of immune function in the caterpillar Spodoptera littoralis

Abstract: Phenoloxidase (PO) is believed to be a key mediator of immune function in insects and has been implicated both in non-self recognition and in resistance to a variety of parasites and pathogens, including baculoviruses and parasitoids. Using larvae of the Egyptian cotton leafworm, Spodoptera littoralis, we found that despite its apparent importance, haemolymph PO activity varied markedly between individuals, even amongst insects reared under apparently identical conditions. Sib-analysis methods were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 26 publications
3
84
2
Order By: Relevance
“…Genetic variation for resistance to parasites has been found in many nonsocial organ-isms (Ebert et al 1998;Carius et al 2001;Little and Ebert 1999Kover and Schaal 2002), and has recently been demonstrated in bumblebees and honeybees (Baer and Schmid-Hempel 2003;Palmer and Oldroyd 2003). Although the mechanism in these latter cases is not yet known, the cellular immune response in insects can vary between genotypes (Carlton et al 1992;Cotter and Wilson 2002). This is thought to contribute to the well-established differences in immune response between bumblebee colonies (König and Schmid-Hempel 1995;Allander and Schmid-Hempel 2000;Mallon et al 2003).…”
Section: Acromyrmex and Pogonomyrmex])mentioning
confidence: 99%
“…Genetic variation for resistance to parasites has been found in many nonsocial organ-isms (Ebert et al 1998;Carius et al 2001;Little and Ebert 1999Kover and Schaal 2002), and has recently been demonstrated in bumblebees and honeybees (Baer and Schmid-Hempel 2003;Palmer and Oldroyd 2003). Although the mechanism in these latter cases is not yet known, the cellular immune response in insects can vary between genotypes (Carlton et al 1992;Cotter and Wilson 2002). This is thought to contribute to the well-established differences in immune response between bumblebee colonies (König and Schmid-Hempel 1995;Allander and Schmid-Hempel 2000;Mallon et al 2003).…”
Section: Acromyrmex and Pogonomyrmex])mentioning
confidence: 99%
“…Genetic variation for resistance to parasites has been found in many nonsocial organ-isms (Ebert et al 1998;Carius et al 2001;Little and Ebert 1999Kover and Schaal 2002), and has recently been demonstrated in bumblebees and honeybees (Baer and Schmid-Hempel 2003;Palmer and Oldroyd 2003). Although the mechanism in these latter cases is not yet known, the cellular immune response in insects can vary between genotypes (Carlton et al 1992;Cotter and Wilson 2002). This is thought to contribute to the well-established differences in immune response between bumblebee colonies (Kö nig and Schmid-Hempel 1995; Allander and Schmid-Hempel 2000; Mallon et al 2003).…”
mentioning
confidence: 99%
“…There is evidence that PO shows genetic variation in a variety of insects (see Fellowes et al 1998;Kraaijeveld & Godfray 1997;Ryder & Siva-Jothy 2001;Cotter & Wilson 2002). The abundance of empirical evidence demonstrating genetic variation for PO levels makes a good case for at least a partial genetic basis for variation in PO levels between populations of Japanese beetles.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to effectively encapsulate an invader is principally determined by the activation of the enzyme phenoloxidase (PO), which catalyses the first step in melanin synthesis. Empirical evidence has linked levels of PO production with resistance to parasites (see Barnes & Siva-Jothy 2000;Gillespie et al 2000;Cotter & Wilson 2002). Such evidence linking PO levels to parasite defence mechanisms predicts that levels of PO should positively correlate with parasite defence.…”
Section: Introductionmentioning
confidence: 99%